A domain specific language for orchestrating user tasks whilst navigation web sites - Firmenich, Sergio Damián (2013)
In this paper we claim that there are a lot of processes over Web applications that require a high level of coordination between individuals and tasks featuring procedures. We propose hereafter a Domain Specific Language (DSL) for describing the asynchronous orchestration users' tasks including manual users' tasks (i.e. simple instructions that tell users what to do during the navigation) and automated tasks (i.e. tasks that can be partially or completely automated by client-side scripts). The approach is illustrated by examples and a case study showing the tools, for which an empiric evaluation is presented.